2017
DOI: 10.1080/21568316.2017.1393772
|View full text |Cite
|
Sign up to set email alerts
|

The Promotion of Responsible Tourism Management Through Digital Media

Abstract: Tourism businesses are increasingly embracing the dynamics of new digital technologies, as they communicate their responsible initiatives through corporate websites, social media platforms and other interactive channels. Therefore, a quantitative study explores the ownermanagers' attitudes on digital media. The methodology integrates measures from technological innovation and corporate social responsibility (CSR) to understand the rationale for using online media to communicate about sustainable and responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 65 publications
(165 reference statements)
1
37
0
2
Order By: Relevance
“…Some researchers have focused on RT from the perspective of business operators [9,22,24,25]. Carasuk, Becken and Hughey [3] explored the factors that make business operators facilitate RT or shift towards RT practices.…”
Section: Responsible Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have focused on RT from the perspective of business operators [9,22,24,25]. Carasuk, Becken and Hughey [3] explored the factors that make business operators facilitate RT or shift towards RT practices.…”
Section: Responsible Tourismmentioning
confidence: 99%
“…Although many business operators have shown an intention to act on RT, Frey and George [24] noted that there are still limits to expanding RT due to major constraints, such as a lack of government support and the perceived costs of implementing RT. In addition, Camilleri [25] stated that digital media plays a critical role in allowing hotel owners and managers to engage in various social activities and ultimately contributes to enhancing hotels' reputation and recognition. Likewise, most previous studies have shown that business operators are aware of the importance of RT and continue to find effective ways to expand RT in the tourism industry.…”
Section: Responsible Tourismmentioning
confidence: 99%
“…Hence, the distribution networks have come a long way from the ticket counter. Evidently, travel and tourism businesses are leveraging themselves with data-driven marketing, as they seek new customers and prospects (Camilleri, 2018a(Camilleri, , 2018b. They may decide to target high-yield customers through elaborated pricing and revenue management systems.…”
Section: The Uses Of Big Data and Analyticsmentioning
confidence: 99%
“…The communications through digital media can be dynamic and in real time. Therefore, online users can increase direct interactions with organizations and other audiences (Camilleri, 2018b;Schultz, Utz & Göritz, 2011). Such interactive communications are often referred to as "viral" because ideas and opinions can spread through the web via word-of-mouth (Hajarian, Camilleri, Diaz & Aedo, 2020).…”
Section: Introductionmentioning
confidence: 99%